Satisfaction with amplification in daily life (SADL) in monaural and binaural hearing aid users - Wan Ahmad, Wan Aslynn Salwani (IIUM Press, 2020)
Introduction:This study was aimed to identify the level of satisfaction in monaural and binaural hearing aid users by using the Malay Satisfaction of Amplification in Daily Life (SADL) questionnaire.Methods: A total of forty (40) hearing aid users fromtheInternational Islamic University, Malaysia (IIUM) Hearing and Speech Clinic at Jalan Hospital Campus, Kuantan, IIUM Medical Specialist Centre and private hearing aid centres participated in this study. Twenty-two (22) of them were monaural users while the rest were binaural hearing aid users.Results:The results were categorized based on the means of each subscales (Positive effects, Negative features, Service & cost and Personal image) as well as mean of global satisfaction scores. Positive effects subscale shows the highest mean score with 5.83 while negative features subscale has the lowest mean with 3.95 regardless of different type of fittings. In addition, it was found that there is no significant difference in the degree of satisfaction in monaural and binauralhearing aid users except for negative feature subscale.Conclusions:Themajority of hearing aid users were satisfied on all four subscales and global score. Assessing patient's satisfaction can be helpful in planning appropriate intervention. Successful hearing aid fitting is correlated with how satisfied the patient is with the outcome provided by the device.